Experimental sleep deprivation as a tool to test memory deficits in rodents - COLAVITO, VALERIA; Fabene, Paolo F.; Grassi Zucconi, Gigliola; Pifferi, Fabien; Lamberty, Yves; Bentivoglio, Marina; Bertini, Giuseppe (Frontiers in Systems Neuroscience, 2013)
Paradigms of sleep deprivation (SD) and memory testing in rodents (laboratory rats and mice) are here reviewed. The vast majority of these studies have been aimed at understanding the contribution of sleep to cognition, and in particular to memory. Relatively little attention, instead, has been devoted to SD as a challenge to induce a transient memory impairment, and therefore as a tool to test cognitive enhancers in drug discovery. The purpose of this article is to provide an overview of the studies that have accurately described methodological aspects of the SD protocol and behavioral paradigm in order to critically assess them and propose SD protocols that could be employed as cognitive challenge. Total SD, partial or state-selective SD (rapid eye movement SD) procedures are first reviewed, followed by procedures to investigate SD-induced impairment of learning and memory consolidation. Thus, a platform of knowledge is here provided for laboratory protocols that could be used to assess the efficacy of drugs designed to improve memory performance in rodents, including rodent models of neurodegenerative diseases that cause cognitive deficits, and Alzheimer’s disease in particular. Issues in the interpretation of such preclinical data and their predictive value for clinical translation are also discussed.